Emesis-induced Sub-periosteal Haematoma: A Case Report. (20th March 2014) - Reid, Jennifer R.; Rajak, Saul N.; Good, C. D.; Brittain, G. Paul
Abstract: Background : Orbital sub-periosteal haematoma (OSH) is usually caused by orbital trauma. We present a case of spontaneous OSH and review the literature on this condition. Methods : We present a case of sub-periosteal haematoma secondary to migraine and vigorous emesis. Discussion : OSH is very rare; this case highlights the clinical features of the condition and that rapid spontaneous resolution can occur. We review the literature on emesis- or valsava-induced OSH and discuss possible mechanisms for its formation in conjunction with migraine.